Socialization of the Utilization of Artificial Intelligence on Education to Improve the Professional Competence of Educators in the Era of Technological Development - Daud, Anshar; Syulhasbiullah, Muh; Nuswardhani, Rr. Sri Karuniari; Masduki, Damayanti; Simatupan, Septian; Widianingsih, Yuliani (Universitas Pahlawan Tuanku Tambusai, 2025)
Community service is organized by the Non-Governmental Organization Noorwangsanegara, located in Bogor, West Java, Indonesia. In the pre-service, it was found that there was a gap in understanding artificial intelligence which is now widely used both in the world of education and in the world of work where students, namely students, will later work. In addition, it is also a challenge for lecturers, especially in improving not only their understanding but also their competence in writing and publishing scientific articles in journals that have a reputation for improving performance in the world of higher education. The problem in this service is how to improve the competence of lecturers through the use of artificial intelligence in writing and reputable publications. The results of the service show that the tendency of participants does not understand the meaning and use of artificial intelligence that can be used in educational activities such as the use of tools that can facilitate work in the world of education. In addition, these tools can also be used in writing articles or disseminating articles through publication in reputable journals. Keywords: Artificial Intelligence, Education, Competence, Technological Development, Socialization